2017
DOI: 10.1177/1040638717704017
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous neoplasms in captive Virginia opossums (Didelphis virginiana): a retrospective case series (1989–2014) and review of the literature

Abstract: This retrospective project summarizes the types of neoplasms identified in Virginia opossums ( Didelphis virginiana) presented to the University of Tennessee, College of Veterinary Medicine (UTCVM) postmortem service in 1989–2014 and serves as a review of the literature. Of the 85 Virginia opossums identified from the UTCVM case database, there were 17 diagnoses of neoplasia from 12 cases (14%). These cases included 8 females, 2 males, and 2 neutered males. All opossums with known ages (11 of 12) were >2 y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Current searches within scientific database platforms showed no evidence of bone neoplasm descriptions in Didelphis albiventris. Pope & Donnell (2017) observed 17 neoplasm cases in Didelphis virginiana, 14 of those categorized as malignant and 3 benign. In the same study, the neoplasm was identified as the reason for the death and euthanasia of 6 animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current searches within scientific database platforms showed no evidence of bone neoplasm descriptions in Didelphis albiventris. Pope & Donnell (2017) observed 17 neoplasm cases in Didelphis virginiana, 14 of those categorized as malignant and 3 benign. In the same study, the neoplasm was identified as the reason for the death and euthanasia of 6 animals.…”
Section: Resultsmentioning
confidence: 99%
“…These animals are affected by infectious and neoplastic disorders (Baker et al 1995). There is limited up-to-date scientific literature about neoplasm in opossums, being restricted to cases in the Didelphis virginiana species (Pope & Donnell 2017). There is also a scarcity of information about the incidence, prevalence, predisponent factors, and behavior of neoplasms in wild animals (Johnson et al 2014, Madsen et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Only three reports of mast cell neoplasia in marsupials could be located; a case of dermal mastocytoma with splenic metastasis in a kowari ( Dasyuroides byrnei ), mastocytoma in an Eastern barred bandicoot ( Parameles gunnii ) and systemic mastocytosis in a Virginia opossum ( Didelphis virginiana ) . In humans, systemic mastocytosis and mast cell leukaemia (MCL) are uncommon diseases.…”
Section: Discussionmentioning
confidence: 99%
“…23 Only three reports of mast cell neoplasia in marsupials could be located; a case of dermal mastocytoma with splenic metastasis in a kowari (Dasyuroides byrnei), 24 mastocytoma in an Eastern barred bandicoot (Parameles gunnii) 20 and systemic mastocytosis in a Virginia opossum (Didelphis virginiana). 25 In humans, systemic mastocytosis and mast cell leukaemia (MCL) are uncommon diseases. The primary diagnostic criterion of MCL in humans is mast cells composing at least 20% of all nucleated cells in bone marrow smears with cytology smears, the gold standard for defining the percentage of mast cells, being preferred over biopsies for histology.…”
Section: Discussionmentioning
confidence: 99%
“…In both species, the GISTs arise due to oncogenic mutations in the KIT tyrosine kinase, which also drives canine cutaneous mast cell tumours [111]. There are also case reports of a mast cell tumour in a llama, which exhibited positive membrane KIT expression [112], and a captive opossum ( Didelphis virginiana ), in which c-KIT positive cancerous cells were found to have spread to distant sites, including the liver, skin, kidney, pancreas and spleen [43].…”
Section: Occurrences Of Spontaneous Metastasis In Non-laboratory Animalsmentioning
confidence: 99%